“Finding my voice again” - women’s experiences of psychological therapy in perinatal secondary care settings: a qualitative study - O’Brien, Jayne; Gregg, Lynsey; Wittkowski, Anja (Frontiers in Psychiatry, 2024)
Introduction: Although women often experience mental health comorbidities in the perinatal period, the evidence-base for psychological therapy across diagnostic boundaries in the perinatal period remains limited. As there is a need to understand experiences of therapy, irrespective of diagnosis, to inform intervention provision, the aims of this study were to explore women's experiences of psychological therapy for perinatal mental health difficulties and to identify the mechanisms that women attributed to the most significant therapeutic change for themselves and/or the mother-infant relationship. Method: Semi-structured interviews were conducted with 16 women who received therapy within specialist perinatal community mental health settings in the Northwest of England, the UK. Interview data were analysed using reflexive thematic analysis. Results: One overarching theme entitled participant life stories were at the heart of therapy was identified alongside three other main themes: 1.) We're in this togethertherapeutic bond and establishing a coherent sense of self, 2.) Surfing the urge to 'fix' feelings -Sitting with emotions improved regulation and 3.) Seeing myself in a new light -Shifting self-blame to selfcompassion enhanced self-efficacy. Theme 1 consisted of three subthemes.Participants described the quality of the therapeutic relationship as the fundamental foundation to (re)connecting with their needs, values and boundaries, which improved their sense of agency, self-esteem, therapeutic engagement and self-understanding. Shifting emotional avoidance to emotional engagement improved their self-regulation. Considering alternative factors that could have contributed to their experiences helped them to defuse selfblame and enhance self-compassion. Finally, changes in their mental health led to positive relational changes in their relationship with their infant and improved communication with partners. Discussion: Sensitivity, engagement and responsivity experienced in the therapist-woman relationship was reported to be mirrored in the mother-infant relationship. Developing a coherent sense of self and self-regulation skills both appeared to heighten women's selfcompassion and empathy for their infants, which also seemed to improve their ability to tolerate uncertainty and mixed emotions within themselves and their infants. The mechanisms of change in the perinatal period are important to consider at a stakeholder, therapist and service management level to parsimoniously and best meet the needs of women and the mother-infant relationship.